Corrigendum to: “Effect of ginger extract and/or fenofibrate on the associated infertility of experimentally induced obese Wistar Albino male rats” [Reprod Biol 26 (2): 101208] - Mohamed H. Elsayed; Samia M. Abd El-Rheem; Essam A. Almadaly; Azza M. Elkattawy; Nasr EL. Nasr; Doaa A. Dorghamm; Walied S. Abdo; Mona Assas; Tarek K. Abouzed; Wael B. El-Domany (Reproductive Biology, 2026)

Effect of ginger extract and/or fenofibrate on the associated infertility of experimentally induced obese Wistar Albino male rats - Mohamed H. Elsayed; Samia M. Abd El-Rheem; Essam A. Almadaly; Azza M. Elkattawy; Nasr EL. Nasr; Doaa A. Dorghamm; Walied S. Abdo; Mona Assas; Tarek K. Abouzed; Wael B. El-Domany (Reproductive Biology, 2026)

Exploring topical atorvastatin hyalurosomal gel as an adjuvant for reducing systemic corticosteroid dosage: a randomized clinical trial in severe oral lichen planus patients - Mahitab Elsayed; Aya Essawy; Radwa M. Ismail; Yasmine Gamil; Mohamed G. Hamed; Dalia Elsabaawy; Eman Abdelhakeem; Doaa Hegazy; Radwa M. A. Abd-Elal (Drug Delivery and Translational Research, 2026)
Oral lichen planus (OLP) is a chronic inflammatory disorder with limited topical treatment options and long-term corticosteroid dependency. This study investigates a novel atorvastatin-loaded hyalurosomal gel (ATV-Hyalugel) as a topical adjuvant to reduce systemic corticosteroid use in severe OLP. The objective of the study is to develop, optimize, characterize ATV-Hyalugel and evaluate its clinical efficacy in a randomized controlled clinical trial. ATV-loaded hyalurosomes (ATV-HAs) were prepared via thin-film hydration and optimized using an I-optimal mixture design (independent variables: phospholipid, Tween 80, and hyaluronic acid; responses: entrapment efficiency (EE%), particle size (PS), and zeta potential (ZP). The optimal formulation was incorporated into a chitosan gel, which was characterized for its pH, rheological behavior, and in-vitro drug release. Four weeks randomized controlled trial (n = 90) compared: group one received standard prednisolone (40 mg/day) while group two received half-dose prednisolone (20 mg/day) in combination with ATV-Hyalugel (topically, three times daily). Pain and ulcer scores were recorded weekly. Between-group comparisons were performed using the Mann–Whitney U test (non-parametric; α = 0.05), and within-group improvement from baseline to Week 4 was assessed using the Kruskal–Wallis test. Optimized ATV-HAs demonstrated high EE% (79.1 ± 0.4%), uniform PS (221.2 ± 5.1 nm), and stable ZP (–31.6 ± 0.2 mV). ATV-Hyalugel exhibited mucosa-compatible pH (6.48 ± 0.2), pseudoplastic rheology, and a sustained release profile dominated by diffusion-driven kinetics. Clinically, group two achieved therapeutic equivalence to group one by Week 2 (p > 0.05), despite receiving 50% less corticosteroid. Both groups showed significant symptom reduction from baseline to Week four (p < 0.0001, Kruskal–Wallis). No adverse events were reported with ATV-Hyalugel. ATV-Hyalugel enables a 50% corticosteroid dose reduction while maintaining clinical efficacy. Its favorable release kinetics and safety profile support its use as an innovative adjuvant therapy for severe OLP.

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

Enhanced Biochemical and Morphological Parameters in Eruca vesicaria by Applications of date-palm seed Extract - Doaa E. Elsherif; Gehad A. Ragab; Sherien E. Sobhy; Elsayed E. Hafez; Asmaa M. Khalifa (Journal of Soil Science and Plant Nutrition, 2025)
The current global context stimulating agroecology and green agriculture need to explore for the novel sustainable and eco-conscious methods for safeguarding plants. The aim of this study is to exploit the rich contents of date palm seeds (DPS) as an appropriate organic elicitor to boost growth and plant secondary metabolism in Eruca vesicaria . The seeds of DPS were utilized in the extraction process using distilled water to create an aqueous extract, which underwent phytochemical characterization. In a pot experiment, Eruca vesicaria seeds were soaked in serial doses (0, 20, 40, 80, and 120 g l ⁻¹) of DPS aqueous extract, and the 21-days old seedlings were collected. DPS extract analysis indicated adequate P and N contents, antioxidant compounds, and exhibited antioxidant activity. The primary components identified in the analysis of DPS were 2-Dodecenal, fatty acids and cyclopentane butyl-acid. Priming with DPS extract significantly improved its bio-stimulating capacity by enhancing fresh and dry biomasses, photosynthetic pigments, and primary metabolites in response to the optimal DSP concentration of 80 g l⁻¹. Stress biomarkers (H 2 O 2 and malondialdehyde (MDA)) were found in the ranges of water-primed control except for the highest dose of DPS extract (120 g l⁻¹). Further, priming with DPS extract increased the secondary metabolites (total phenolics and flavonoids) besides the activity of polyphenol oxidase (PPO), suggesting an enhanced cell redox system. The expression patterns of a series of specific key genes included in secondary metabolism modulation as, phenylalanine ammonia lyase ( PAL ), chalcone synthase ( CHS ), chalcone isomerase ( CHI ), flavonol synthase ( FLS ), and deoxyxylulose phosphate reductoisomerase ( DXR ), were activated following treatments with DPS extract. Overall, the present study underscores that the application of DPS extract can stimulate the growth and bioactive constituents of Eruca vesicaria , thus elevating its potential as a nutraceutical and medicinal value.

Vinpocetine and Lactobacillus Attenuated Rotenone-Induced Parkinson’s Disease and Restored Dopamine Synthesis in Rats through Modulation of Oxidative Stress, Neuroinflammation, and Lewy Bodies Inclusion - Hanan M. Hassan; Hadeer O. Abou-Hany; Ahmed Shata; Doaa Hellal; Ahmed M. El-Baz; Zeinab H. ElSaid; Amira A. Haleem; Nesreen Elsayed Morsy; Rawan M. Abozied; Bassant M. Elbrolosy; Sally Negm; Attalla F. El-kott; et al. (Journal of Neuroimmune Pharmacology, 2025)

Marine Smenospongia extract mitigated co-infection with Trichodina sp. and Flavobacterium columnare in Nile tilapia: insights into promoting growth performance, immune, antioxidant and autophagy defenses, and suppression of endoplasmic reticulum stress-related genes - Doaa Ibrahim; Ioan Pet; Reham G. A. Anter; Abdelwahab A. Abdelwarith; Mona Mohammed I. Abdel Rahman; Basant M. Shafik; Elsayed M. Younis; Asmaa Basiony; Shimaa A. E. Atwa; Aya Sh. Metwally; Heba A. Tolba; Mirela Ahmadi; et al. (Frontiers in Marine Science, 2024)
Identifying novel natural sources from the marine environment with unique immunomodulatory and antioxidant efficacies is of interest in intensive fish farming. In this sense, marine sponge extract derived from Smenospongia (SS-extract) was tested for its potential anti-inflammatory, antioxidant and antimicrobial activities during the concurrent infection with Trichodina sp. and Flavobacterium columnare in Nile tilapia. A total of 625 Nile tilapia fingerlings were distributed into five groups: the control group (with no additives) and four groups fed the control diet fortified with SS-extract at 50, 100, 150, and 200 mg/kg, respectively, for 60 days. The parasitic challenge with Trichodina sp was done at the endpoint of the feeding trial and at 7 days post-infection (dpi); the fish were coinfected with F. columnare . A significant improvement in growth-related parameters of Nile tilapia was detected in the groups that received SS-extract at the levels of 150 and 200 mg/kg. The scavenging ability for free radicals (2,2′-azino-bis-3-ethylbenzthiazoline-6-sulfonic acid (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPPH)) was maximized with higher SS-extract supplementation levels. Simultaneously, the antioxidant defense of the Nile tilapia fed 150 and 200 mg/kg was augmented with a decline in oxidation-associated indicators [reactive oxygen species (ROS), hydrogen peroxide (H 2 O 2 ), and malondialdehyde (MDA)]. The higher concentrations of SS-extract in the feed potentiated the immune response of Nile tilapia before infection and even after coinfection and was paralleled by a subsiding in the exaggerated inflammatory response after concurrent infection. Concurrently, the mRNA expression of autophagy-encountered genes ( Atg5 and 12, LC3-II and BCLN1 ) had its highest expression in the fish fed the 200 mg/kg diet with the lowest expression of the mTOR gene in the same fish. The lowest infection intensity and rate and mucus score were displayed in fish fed 200 mg/kg SS-extract at 20 dpi. Interestingly, higher levels of SS-extract triggered antimicrobial peptides (upregulation of Hepcidin and β-defensin-1). In contrast, excessive expression of endoplasmic reticulum genes ( atf4 , JAK1 , PERK , and eif2α ) in the control infected group was downregulated by 200 mg/kg of SS-extract. The quantification of F. columnare indicated that columnaris coinfection severity displayed its lowest rate in the group supplemented with 200 mg/kg of SS-extract. In conclusion, a strategic siting based on fortification of the diet of Nile tilapia with SS-extract was elucidated to reinforce its immune and antioxidant defenses during a concurrent infection.

Current progress toward synthetic routes and medicinal significance of quinoline - Wesam S. Shehab; Mostafa M. K. Amer; Doaa A. Elsayed; Krishna Kumar Yadav; Magda H. Abdellattif (Medicinal Chemistry Research, 2023)
Quinoline motifs are essential in several pharmacological active heterocyclic compounds due to their various applications in medicinal and industrial chemistry. Furthermore, there are greater societal expectations in the current scenario that synthetic and medicinal chemists should produce greener and more sustainable chemical processes. Therefore, this mini-review article highlights the traditional and green synthetic approaches of quinoline and its analogs, including multicomponent one-pot reactions and solvent-free reaction conditions utilizing microwave and ultraviolet irradiation-promoted synthesis using eco-friendly and safe reusable catalysts, in addition to discussing the medicinal importance of quinoline derivatives such as anticancer, antioxidant, anti-inflammatory, antimalarial, anti-SARS-CoV-2, and antituberculosis activities within the period from 2011 till 2021. Therefore, the quinoline scaffolds signify a unique class of pharmacophores present in various therapeutic agents.

Silymarin inhibits the progression of Ehrlich solid tumor via targeting molecular pathways of cell death, proliferation, angiogenesis, and metastasis in female mice - Maggie E. Amer; Maher A. Amer; Azza I. Othman; Doaa A. Elsayed; Mohamed Amr El-Missiry; Omar A. Ammar (Molecular Biology Reports, 2022)